2019
DOI: 10.1021/acsomega.9b00162
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Druggability Assessment of Human DNA Glycosylases

Abstract: Due to a polar or even charged binding interface, DNA-binding proteins are considered extraordinarily difficult targets for development of small-molecule ligands and only a handful of proteins have been targeted successfully to date. Recently, however, it has been shown that development of selective and efficient inhibitors of 8-oxoguanine DNA glycosylase is possible. Here, we describe the initial druggability assessment of DNA glycosylases in a computational setting and experimentally investigate several meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 114 publications
1
24
0
Order By: Relevance
“…Yet this situation is ideal in the case of a synthetic lethality interaction between the pathologic context and DNA glycosylase [58,59]. Over the last few years, the search for inhibitors of DNA glycosylases hNeil1 (hNeil2) and hOgg1 has become a very active field [18][19][20][21]56,60,61]. We started this research in 2014 by discovering that 2-thioxanthine is an irreversible inhibitor of the bacterial enzymes Fpg and Nei and the human enzyme hNeil2, three enzymes belonging to the Fpg/Nei DNA glycosylase structural superfamily having a zinc finger (ZnF) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yet this situation is ideal in the case of a synthetic lethality interaction between the pathologic context and DNA glycosylase [58,59]. Over the last few years, the search for inhibitors of DNA glycosylases hNeil1 (hNeil2) and hOgg1 has become a very active field [18][19][20][21]56,60,61]. We started this research in 2014 by discovering that 2-thioxanthine is an irreversible inhibitor of the bacterial enzymes Fpg and Nei and the human enzyme hNeil2, three enzymes belonging to the Fpg/Nei DNA glycosylase structural superfamily having a zinc finger (ZnF) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Druggability predictions using DoGSite are based on rigid protein structures, not allowing for flexibility typically induced by larger natural substrates or specifically designed small molecules (Michel et al, 2019). Another aspect is the potential existence of allosteric sites.…”
Section: Automated Arm -Step 2: Cryptosite and Ftmap Confirm Druggablmentioning
confidence: 99%
“…In case of the NUDIX proteins, NUDT22 for example showed to have high scores in DogSite and FTMap with CryptoSite confirming flexibility around two closely related sites. Further, in the past we have shown that comparing different crystals structures of the same protein can allow for the observation of targetable conformations more suitable smallmolecule development (Michel et al, 2019). With the open access deposition of all screening data by the SGC, a similar albeit more time consuming approach is possible for a number of NUDIX proteins 1 .…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…The DSF assay was done according to the protocol previously described by Michel et al [ 46 ]. In Brief, 0.2 μL triplicates in a 2:1 dilution of a 10 mM TH5487 solution and a DMSO control were spotted in White BioRad 384-well plates.…”
Section: Methodsmentioning
confidence: 99%